2019
DOI: 10.1101/682013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide association study provides new insights into the genetic architecture and pathogenesis of heart failure

Abstract: Heart failure (HF) is a leading cause of morbidity and mortality worldwide1. A small proportion of HF cases are attributable to monogenic cardiomyopathies and existing genome-wide association studies (GWAS) have yielded only limited insights, leaving the observed heritability of HF largely unexplained2–4. We report the largest GWAS meta-analysis of HF to-date, comprising 47,309 cases and 930,014 controls. We identify 12 independent variant associations with HF at 11 genomic loci, all of which demonstrate one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 84 publications
0
20
0
Order By: Relevance
“…This ability to study CMs themselves is especially important given that GWAS studies for heart failure have revealed little of the genetic architecture of the disease. While pedigree analysis suggests that the heritability of heart failure is 26% -34% [68], two recent, large-scale GWAS identified only eleven [105] and three [6] genomic loci associated with heart failure. This could be due to a lack of quantitative measurements of heart failure, complex etiologies, or the significant environmental contributions to developing heart failure [97].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This ability to study CMs themselves is especially important given that GWAS studies for heart failure have revealed little of the genetic architecture of the disease. While pedigree analysis suggests that the heritability of heart failure is 26% -34% [68], two recent, large-scale GWAS identified only eleven [105] and three [6] genomic loci associated with heart failure. This could be due to a lack of quantitative measurements of heart failure, complex etiologies, or the significant environmental contributions to developing heart failure [97].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike atrial fibrillation, GWAS for heart failure have not identified many association signals, likely due to the highly heterogeneous nature of the disease. Two recent meta-analyses identified 3 and 13 genes, respectively [6,105]. Three of the genes associated with heart failure had treatment cASE: FAM241A in 5 conditions (copper, dexamethasone, insulin, ca↵eine, and vitamin A); BAG3 in 5 conditions (dexamethasone, ca↵eine, vitamin A, nicotine, and aldosterone); and KLHL3 in triclosan.…”
Section: Biological and Clinical Significance Of Allele-specific Expression Across Cell Types And Treatmentsmentioning
confidence: 99%
“…This ability to study CMs themselves is especially important given that GWAS studies for heart failure have revealed little of the genetic architecture of the disease. While pedigree analysis suggests that the heritability of heart failure is 26% -34% [65], two recent, large-scale GWAS identified only eleven [102] and three [6] genomic loci associated with heart failure. This could be due to a lack of quantitative measurements of heart failure, complex etiologies, or the significant environmental contributions to developing heart failure [94].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike atrial fibrillation, GWAS for heart failure have not identified many association signals, likely due to the highly heterogeneous nature of the disease. Two recent meta-analyses identified 3 and 13 genes, respectively [6,102]. Three of the genes associated with heart failure had treatment cASE: FAM241A in 5 conditions (copper, dexamethasone, insulin, caffeine, and vitamin A); BAG3 in 5 conditions (dexamethasone, caffeine, vitamin A, nicotine, and aldosterone); and KLHL3 in triclosan.…”
Section: Biological and Clinical Significance Of Allele-specific Exprmentioning
confidence: 99%
“…The data of LDL, HDL, TG, TC were from the meta-analysis by cristen J willer et al (17). HF data was derived from a large-scale GWAS meta-analysis involving 47,309 cases and 930,014 controls (18). AF data came from a meta-analysis of more than 500,000 participants (19).…”
Section: Data Sourcesmentioning
confidence: 99%